THE INFLUENCE OF NUTRITION AWARENESS ON COW'S MILK CONSUMPTION IN INDONESIA - Nadia Rilla Dzakiyya (RADJA PUBLIKA, 2025)
This study aims to determine the level of nutritional awareness among Indonesian people in consuming cow's milk. The method used in this study is quantitative analysis with Ordinary Least Square (OLS) data processing techniques. The type of data used is Time Series data, namely 2002 to 2022, in a period of approximately 20 years. This study uses data on average milk consumption as the dependent variable and data on per capita income, and average length of schooling as independent variables. The data used comes from the Central Statistics Agency (BPS), the Organisation for Economic Co-operation and Development (OECD), and the World Bank. The results of the analysis show that there is only 1 independent variable that significantly influences the average consumption of cow's milk, where the level of education plays an important role in shaping consumer behavior related to cow's milk. A higher level of education can increase nutritional awareness and public knowledge about the benefits of cow's milk.